Reverse Lymphatic Mapping and Immediate Microsurgical Lymphatic Reconstruction Reduces Early Risk of Breast Cancer–Related Lymphedema. Issue 5 (7th March 2022) - Weinstein, Brielle; Le, Nicole K.; Robertson, Ellen; Zimmerman, Amanda; Tavares, Tina; Tran, Thanh; Laronga, Christine; Panetta, Nicholas J.
Abstract : Background: Breast cancer–related lymphedema is a progressive disease that poses tremendous physical, psychosocial, and financial burden on patients. Immediate lymphaticovenular anastomosis at the time of axillary lymph node dissection is emerging as a potential therapeutic paradigm to decrease the incidence of breast cancer–related lymphedema in high-risk patients. Methods: Eighty-one consecutive patients underwent reverse lymphatic mapping and, when feasible, supermicrosurgical immediate lymphaticovenular anastomosis at the time of axillary lymph node dissection at a tertiary care cancer center. Patients were followed prospectively in a multidisciplinary lymphedema clinic (plastic surgery, certified lymphatic therapy, dietary, case management) at 3-month intervals with clinical examination, circumferential limb girth measurements, and bioimpedance spectroscopy. An institutional control cohort was assessed for the presence of objectively diagnosed and treated breast cancer–related lymphedema. Data were analyzed by a university statistician. Results: Seventy-eight patients met inclusion, and 66 underwent immediate lymphaticovenular anastomosis. Mean follow-up was 250 days. When compared to a retrospective control group, the rate of lymphedema in patients who underwent immediate lymphaticovenular anastomosis was significantly lower (6 percent versus 44 percent; p < 0.0001). Patients with 6-month follow-up treated with combined adjuvant radiation therapy and chemotherapy had significantly greater risk of developing breast cancer–related lymphedema ( p = 0.04) compared to those without combined adjuvant therapy. Arborized anastomotic technique had a statistically shorter operative time than end-to-end anastomosis ( p = 0.005). Conclusions: This series of consecutive patients demonstrate a 6 percent incidence of early-onset breast cancer–related lymphedema with immediate lymphaticovenular anastomosis and an increased risk in those undergoing combined adjuvant treatment. These early data represent an encouraging and substantial decrease of breast cancer–related lymphedema in high-risk patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.